Human-Computer Systems Interaction: Backgrounds and Applications 3 - Hippe, Zdzisław S.; Hippe, Zdzisław S.; Kulikowski, Juliusz L.; Kulikowski, Juliusz L.; Mroczek, Teresa.; Mroczek, Teresa.; Wtorek, Jerzy.; Wtorek, Jerzy. (Advances in Intelligent Systems and Computing,, 2014)
This book contains an interesting and state-of the art collection of papers on the recent progress in Human-Computer System Interaction (H-CSI). It contributes the profound description of the actual status of the H-CSI field and also provides a solid base for further development and research in the discussed area. The contents of the book are divided into the following parts: I. General human-system interaction problems; II. Health monitoring and disabled people helping systems; and III. Various information processing systems. This book is intended for a wide audience of readers who are not necessarily experts in computer science, machine learning or knowledge engineering, but are interested in Human-Computer Systems Interaction. The level of particular papers and specific spreading-out into particular parts is a reason why this volume makes fascinating reading. This gives the reader a much deeper insight than he/she might glean from research papers or talks at conferences. It touches on all deep issues that currently preoccupy the entire field of H-CSI.  .